Th THE INFLUENCE OF INDUSTRIAL AGGLOMERATION, LABOR FORCE, AND HUMAN RESOURCE INVESTMENT ON ECONOMIC GROWTH IN SUMATRA IN THE PERSPECTIVE OF ISLAMIC ECONOMICS IN 2019-2023 - Olifia, Febrina; Budimansyah, Budimansyah; Zuliansyah, A (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Within the framework of Islamic economics, economic development focuses not only on growth but also on equitable distribution of welfare and social justice. Industrial agglomeration, labor force, and human capital investment are factors believed to influence regional economic growth. This study aims to analyze the effect of industrial agglomeration, labor force, and human capital investment on economic growth in Sumatra Island during the period of 2019–2023 from the perspective of Islamic economics. The study uses panel data from 10 provinces in Sumatra with a saturated sampling method. Data analysis was conducted using panel regression with the help of EViews 10 software. The results show that simultaneously, the three independent variables affect economic growth. However, partially, only industrial agglomeration has a significant effect, while labor force and human capital investment do not have a significant impact. From the perspective of Islamic economics, these findings highlight the importance of integrated and just industrial development, along with the need to improve the quality of the labor force and education in line with the values of justice, public interest (maslahah), and equity.